2017
DOI: 10.24191/smrj.v14i2.5496
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Basic Numeracy Learning Application for Children with Autism: A Pilot Study

Abstract: Children with autism  have various difficulties in developing cognitive abilities and attaining new knowledge. However, it is essential they obtain a competence approach in order to achieve independence. The state of art has shown  that a significant aspiration for children with autism  is to become independent. Part of attaining independence includes achieving skills that allow for self-determination and involvement in social activities. Hence, it is essential for every child with autism to acquire basic nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Referring to similar to our research's results indicating that mobile learning in Special Education has a positive effect Campigotto et al (2013), Skiada et al (2014), Rivera et al (2016), Zhang et al (2016), Kamaruzaman, et al (2017), Pitchford et al (2018) and Novack et al (2018) state that students with various learning difficulties made progress in language and mathematics, were motivated and interested in learning, felt important and gained confidence, were attracted to practicing and doing exercises, attained their learning interest and achieved self-independence.…”
Section: Discussionsupporting
confidence: 83%
“…Referring to similar to our research's results indicating that mobile learning in Special Education has a positive effect Campigotto et al (2013), Skiada et al (2014), Rivera et al (2016), Zhang et al (2016), Kamaruzaman, et al (2017), Pitchford et al (2018) and Novack et al (2018) state that students with various learning difficulties made progress in language and mathematics, were motivated and interested in learning, felt important and gained confidence, were attracted to practicing and doing exercises, attained their learning interest and achieved self-independence.…”
Section: Discussionsupporting
confidence: 83%
“…The latest scientific articles in journals, books, and proceedings by Ramadhani, Kamaruzzaman showed that the education of autistic children requires multiple approaches and methods (Ramadhani, Bahri, & Silviyanti, 2019) in every educational process (Kamaruzaman, Noor, & Azahari, 2017). One method that could be effective involves using social stories (Alataibi, Dimitriadi, & Kemp, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have suggested that electronic devices such as iPads and smartphones installed with assistive apps are effective in teaching children with ASD when additional features such as audio and video are included in the provided content [ 8 ]. Previous studies have found that children can learn numeracy skills through digital devices with touchscreen technology [ 9 , 10 ]. Many children with ASD are drawn toward computers as they tend to be visual learners.…”
Section: Introductionmentioning
confidence: 99%